Unilateral Third Head of Biceps Brachii with Associated Neurovascular Variants in both the Upper Limbs of a Single Cadaver - Poornima, C Swathi; Bhagyalakshmi, B (Asian Journal of Medical Sciences, 2013)
During routine undergraduate dissection in the upper extremities of a 65 years old male cadaver in the department of Anatomy at Dr. PSIMS & RF, coexistence of muscular and neurovascular variants were identified .Muscular variations included presence of additional head(third) of biceps brachii in the left arm, accompanied with medially positioned median nerve in relation to brachial artery bilaterally . Teres minor muscle was not identified and the origin of long head of triceps brachii extended upto the lateral border of scapula on the left side. Both the medial cutaneous nerves of arm and forearm arouse from a single trunk bilaterally. In the right limb the axillary artery showed only four branches instead of six branches, with common trunk for thoraco-acromial and lateral thoracic artery and common trunk for subscapular and posterior circumflex humeral artery. Knowledge of coexistence of these variations would of profound importance surgically and clinically, especially in limb injuries and surgical repairs. DOI: http://dx.doi.org/10.3126/ajms.v5i1.7391 Asian Journal of Medical Science Vol.5(1) 2014 pp.81-85